You are on page 1of 5

The Quotient Rule

A special rule, the quotient rule , exists for differentiating quotients of two functions. This unit illustrates this rule. In order to master the techniques explained here it is vital that you undertake plenty of practice exercises so that they become second nature. After reading this text, and/or viewing the video tutorial on this topic, you should be able to: • state the quotient rule • differentiate quotients of functions

Contents
1. Introduction
dv v du − u dx u dy dx 2. The quotient rule: if y = then = v dx v2

2 2

© skillbank solutions limited 2010
All references to © mathtutor on subsequent pages should be read as © skillbank solutions limited 2010

In this unit we will state and use the quotient rule. 2. For example. Introduction Functions often come as quotients.1. du = − sin x dx We now put all these results into the given formula: dv v du − u dx dy dx = dx v2 dv = 2x dx mathtutor project: November 9. So u = cos x v = x2 We now write down the derivatives of these two functions. by which we mean one function divided by another function. The quotient rule The rule states: Key Point The quotient rule: if y = u then v v du − u dv dy = dx 2 dx dx v Let’s see how the formula works when we try to differentiate y = Example Suppose we want to differentiate y = cos x . x2 cos x . x2 We have identified u as cos x and v as x2 . cos x y= 2 x u We write this as y = where we identify u as cos x and v as x2 . 2004 2 .it is called the quotient rule. v There is a formula we can use to differentiate a quotient .

Example Suppose we want to differentiate y = tan x. 2x − 7 We recognise this as a quotient and identify u as x2 + 6 and v as 2x − 7. dy x2 · (− sin x) − cos x · 2x = dx (x2 )2 Notice that there is a minus sign and an x in both terms of the numerator (the top line). We have found the required derivative. 2004 . −x(x sin x + 2 cos x) dy = dx x4 −(x sin x + 2 cos x) = x3 by cancelling the factor of x in the numerator and the denominator.Quote the formula everytime so that you get to know it. u = x2 + 6 Differentiating du = 2x dx Quoting the formula: v du − u dv dy = dx 2 dx dx v So (2x − 7) · 2x − (x2 + 6) · 2 dy = dx (2x − 7)2 = = 2(2x2 − 7x − x2 − 6) (2x − 7)2 2(x2 − 7x − 6) (2x − 7)2 dv =2 dx v = 2x − 7 In the following Example we will use the quotient rule to establish another result. Example Suppose we want to differentiate y = x2 + 6 . 3 mathtutor project: November 9. So we can take out a common factor of −x.

So dy 1 = dx cos2 x This can be written as sec2 x because the function sec x is defined to be Example Suppose we want to differentiate y = sec x. 1 The function sec x is defined to be . 2004 4 .Recall that tan x = sin x so we have a quotient in which cos x u = sin x v = cos x dv = − sin x dx So Quoting the formula: du = cos x dx v du − u dv dy = dx 2 dx dx v So dy cos x · cos x − sin x · (− sin x) = dx cos2 x 2 2 cos x + sin x = cos2 x The top line can be simplified using the standard result that cos2 x + sin2 x = 1. cos x mathtutor project: November 9. a quotient. cos x Taking u=1 v = cos x dv du =0 = − sin x dx dx Quoting the formula: v du − u dv dy = dx 2 dx dx v So dy cos x · 0 − 1 · (− sin x) = dx cos2 x sin x = cos2 x We can write this answer in an alternative form: 1 sin x dy = · dx cos x cos x = sec x tan x We now have another standard result: if y = sec x then dy = sec x tan x. dx 1 . that is.

then dy = sec2 x dx if y = sec x.Key Point if y = tan x. then dy = sec x tan x dx Exercises Find the derivative of each of the following: cos x 2x + 1 3x − 4 sin x b) c) d) a) 2 x x 3x − 4 2x + 1 e) e2x x f) e−3x x2 + 1 g) x2 − 3 2x + 1 h) 2x + 1 x2 − 3 Answers a) e) x cos x − sin x x2 (2x − 1)e2x x2 b) f) −(x sin x + 2 cos x) x3 −(3x2 + 2x + 3)e−3x (x2 + 1)2 c) g) −11 (3x − 4)2 2(x2 + x + 3) (2x + 1)2 d) h) 11 (2x + 1)2 −2(x2 + x + 3) (x2 − 3)2 5 mathtutor project: November 9. 2004 .